2016
DOI: 10.1634/theoncologist.2015-0406
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient Blood Management Program and an Outpatient Anemia Management Protocol on Red Cell Transfusions in Oncology Inpatients and Outpatients

Abstract: Background. Patient blood management (PBM) programs are associated with reduced transfusion usage, reduced hospital costs, and improved patient outcomes. The application of PBM principles in patients with malignant disease might achieve similar results. However, this population presents unique challenges. The aim of the present study was to investigate the impact of a PBM program on blood usage and patient outcomes in cancer patients, particularly in the setting of restricted use of erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…The finding of no significant difference in mortality at lower haemoglobin levels in those not transfused may contribute to discussion surrounding tolerance of lower transfusion thresholds . The acceptance of lower haemoglobin levels in challenging patient populations adds to the feasibility of more restrictive haemoglobin thresholds being studied in RCTs, further avoiding exposure to red blood cells .…”
Section: Discussionmentioning
confidence: 99%
“…The finding of no significant difference in mortality at lower haemoglobin levels in those not transfused may contribute to discussion surrounding tolerance of lower transfusion thresholds . The acceptance of lower haemoglobin levels in challenging patient populations adds to the feasibility of more restrictive haemoglobin thresholds being studied in RCTs, further avoiding exposure to red blood cells .…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to reduce RBC transfusion burden include single unit transfusion and a restrictive transfusion policy defined by use of a hemoglobin transfusion trigger of 7.0–8.0 g/dL . Gross et al observed a significant reduction of the mean number of RBC transfusions per patient after implementation of a patient blood management program in their cancer center (U.S.) despite marked decline in ESA use because of warnings issued by the Food and Drug Administration and regulatory restrictions . Excluding patients with leukemia, 198 patients received a mean of 5.3 RBC units during a 5‐year period from January 2008 to July 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Широкое внедрение МКП в практику здравоохранения имеет преимущества как на уровне пациента, так и на уровне общества в целом, поскольку оно улучшает ключевые показатели эффективности лечения пациентов, одновременно снижая потребление продуктов крови и затраты на него [34][35][36][37]. При эффективном МКП, как, например, внутривенном введении железа в пред-и постоперационных условиях или вне хирургической среды, пациентам, как правило, требуется меньше гемотрансфузий донорских компонентов крови [38,[136][137][138][139], что влечет сокращение риска осложнений, вызываемых переливанием крови.…”
Section: результаты лечения отмеченные при мкп и терапевтических схеunclassified